Response of giant foxtail and wild proso millet to artificial light quality alteration - Bisikwa, Jenipher; Becker, Roger L.; Fritz, Vince A.; Natukunda, Kevin; Natukunda, Martha I. (Journal of Scientific Agriculture, 2021)
Light is an essential requirement for proper plant growth and development. Growth chamber experiments were conducted to determine whether artificial alteration of light quality (reducing the red to far-red ratio-R:FR) differentially affected the growth and development of giant foxtail and wild proso millet, two troublesome annual grass weeds in the United States. Growth phenotypes of both weeds were examined under two R:FR regimes (0.28-reduced R:FR and 1.12-unaltered R:FR) in the absence of competition (control conditions) and under intraspecific and interspecific competition. The reduced R:FR simulated shaded (below-canopy) R:FR conditions in the field while the unaltered R:FR treatment simulated direct sunlight (above-canopy) conditions. Averaged across weed species, reducing the R:FR increased plant height, but reduced tiller production and above-ground biomass under no plant competition (P<0.05). In the presence of competition, reducing the R:FR increased plant height and internode length but reduced the number of tillers and leaf area across weed species. No phenotypic differences were observed for weeds tested under intraspecific or interspecific competition. Our study has shown that the response of both weeds to artificial R:FR alteration is similar to that observed under shaded field conditions. Therefore, by replacing bordering plants with a crop, controlled experiments can be used to test the effect of crop canopies on weed suppression when selecting cultivars to be planted in areas where certain weed species are prevalent, minimizing weed-related yield losses.